2005
DOI: 10.4049/jimmunol.174.3.1501
|View full text |Cite
|
Sign up to set email alerts
|

Ig-Independent Igβ Expression on the Surface of B Lymphocytes after B Cell Receptor Aggregation

Abstract: In order for humoral immune responses to develop, B cells must be able to recognize, bind, and internalize Ags. These functions are performed by the BCR, which is also responsible for initiating and transducing activation signals necessary for B cell proliferation and differentiation. We have examined surface expression patterns of individual components of the BCR following anti-Ig- and Ag-induced aggregation. Specifically, the localization and expression levels of the Ag-binding component, surface Ig (sIg), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Most sIg-dissociated Ig␣/␤ heterodimers remain on the cell surface (39,40); however, our preliminary investigation indicated that Ig␣/␤ did not remain in association with CD20. BCR dissociation from CD20 may be necessary to allow CD20 to remain at the cell surface while antigen-bound receptors are internalized, or it may regulate the function of CD20.…”
Section: Discussionmentioning
confidence: 81%
“…Most sIg-dissociated Ig␣/␤ heterodimers remain on the cell surface (39,40); however, our preliminary investigation indicated that Ig␣/␤ did not remain in association with CD20. BCR dissociation from CD20 may be necessary to allow CD20 to remain at the cell surface while antigen-bound receptors are internalized, or it may regulate the function of CD20.…”
Section: Discussionmentioning
confidence: 81%
“…It is thus feasible that the Igβ/CD19 module also plays a role on normal B cells. For example, it has been found that after their activation, splenic B cells rapidly internalize their BCR but still can be stained with anti‐Igβ antibodies although they are mIg negative (Kremyanskaya & Monroe, 2005). It was suggested that upon ligation, the BCR complex is destabilized so that the mIg molecule is separated from the Igα/Igβ heterodimer which stays alone on the B‐cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The ppc1-5/ 1 B cells exhibited increased levels of MHC class II, CD69, and B7.2, and decreased level of CD79b (Ig-␤ chain of the BCR) (Fig. 7A), indicating BCR engagement/activation (57)(58)(59)(60).…”
Section: The Phenotype Of Ppc1-5h/ 1 B Cellsmentioning
confidence: 99%